Haploidentical vs. HLA-matched donor hematopoietic stem-cell transplantation for pediatric patients with acute lymphoblastic leukemia in second remission: A collaborative retrospective study of the Spanish Group for Bone Marrow Transplantation in Children (GETMON/GETH) and the Spanish Childhood Relapsed ALL Board (ReALLNet) - Moreno, Celia; Ramos-Elbal, Eduardo; Velasco, Pablo; Aguilar, Yurena; Gonzáález Martínez, Berta; Fuentes, Carolina; Molinos, Águeda; Guerra-García, Pilar; Palomo, Pilar; Verdu, Jaime; Adán Pedroso, Rosa María; Vagace, José Manuel; et al. (Frontiers in Pediatrics, 2023)
Introduction Studies addressing the role of haploidentical as alternative to HLA-matched donors for stem cell transplantation (SCT) often include patients with diverse hematological malignancies in different remission statuses. Methods We compared outcomes of children with acute lymphoblastic leukemia (ALL) undergoing SCT in second complete remission (CR2) from haploidentical (n = 25) versus HLA-matched donor (n = 51). Results Patients were equally distributed across both groups according to age, immunophenotype, time to and site of relapse, relapse risk-group allocation, and minimal residual disease (MRD) before SCT. Incidence of graft failure, acute graft versus host disease (GVHD), and other early complications did not differ between both groups. We found no differences in overall survival (58.7% versus 59.5%; p = .8), leukemia free survival (LFS) (48% versus 36.4%; p = .5), event free survival (40% versus 34.4%; p = .69), cumulative incidence (CI) of subsequent relapse (28% versus 40.9%; p = .69), treatment related mortality (24% versus 23.6%; p = .83), CI of cGVHD (4.5% versus 18.7%; p = .2), and chronic GVHD-free and leukemia-free survival (44% versus 26.3%; p = .3) after haploidentical donor SCT. Chronic GVHD (HR = 0.09; p=.02) had protective impact, and MRD ≥ 0.01% before SCT (HR = 2.59; p=.01) had unfavorable impact on LFS. Discussion These results support the role of haploidentical donor SCT in children with ALL in CR2.